Semper Fidelis: Some Values of The Marine Retiree Group - Virienia Puspita (Humaniora, 2016)
This research tried to reveal the group values of Marine retiree Depok, which has done by using symbolic convergence theory as the main theory. The aims of this research were to find and identify fantasy themes, rhetorical vision and group values of Marine retiree group in Depok. This study was based on a foundation of interpretative paradigm with qualitative research methods to find a fantasy theme that emerged in the group through the method of analysis of fantasy by Bormann. The results of the this study indicate the stories of Marine retiree in Depok are the bridge of experience of Marine retiree in the past with present time. Besides that, it is the formation of behavior in forms of values, culture and communication behavior of them. From the analysis theme shows that the group values of Marine retiree in Depok has manifested by universal's idealism value of Marines Semper Fidelis (loyalty), sacrifice, dedication, pride and self esteem. The group rhetorical visions are pride of the group, desire for being accepted and close to their group's identity.